KAJIAN TINGKAT PENERIMAAN KONSUMEN TERHADAP PRODUK SASATE IKAN PATIN (Pangasius hypophthalamus) - Syahrul '; Dewita '; Sukirno Mus (Fakultas Perikanan dan Kelautan, Universitas Riau, 2010)
This research was conducted in the Fisheries Technology Laboratory andthe Laboratory of Food Chemistry at the Faculty of Fisheries and Marine SciencesUniversity of Riau. Research goal was to find out the level of consumeracceptance of patin fish sasate formulation with a different flavor. Researchresults were expected to provide information on the formulation ingredients sasatepatin fish that could be received by consumers. Research method was ofexperiment, namely to patin fish processing sasate formulation with differentspices. The design used was the Complete Random Design non-factorial withthree stage treatment formulation flavor that was different formulation ingredientsA0 (control), formulation ingredients A1 and A2 formulation ingredients withrecycling as much as 3 times, and there were 9 experimental units.Sasate food is typically derived from the Banten area. Giving the namesasate based raw materials as a toaster fish first sasate patin fish with theformulation of different ingredients are generally preferred by consumers. Patinfish Sasate the most preferred consumer is sasate patin fish with flavorformulation A1. Characteristics of patin fish sasate the most preferred consumerbrowning was yellow, very fragrant flavor and flavor fish less, think more flavourfeel and taste fish less, and have a rough texture. The average value analysisproksimat sasate patin fish with formulation A1 has a flavor the water content68.85%, protein content 8.36%, and fat content 9.70%.